How Servant Leadership Handles Turnover In Government Internal Audit Body: The Role Of Job Embeddedness And Job Satisfaction - Mohamad Eran Zhahranshah; Fanny Martdianty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study explored the influence of servant leadership on turnover intention among internal auditors in the Indonesian government. Employee turnover in the public sector poses a serious threat to organizations, including a prominent government internal audit institution which is responsible for internal audit and governance oversight in the government of The Republic of Indonesia. This study used a cross-sectional method with purposive non-probability sampling. Questionnaires were distributed to 265 respondents. Data analysis employed CB-SEM revealed that job embeddedness plays a crucial role in strengthening the effect of servant leadership on turnover intention. In contrast, job satisfaction showed no significant impact on turnover intention. These findings provide important empirical insights for the government internal audit institution in developing human resource management strategies, particularly in enhancing employee retention to minimize turnover risks that could lead to substantial organizational costs.